Reproductive Outcome Following Thawed Embryo Transfer in Management of Ovarian Hyperstimulation Syndrome - Absalan, Forouzan (Avicenna Research Institute, 2013)
BACKGROUND: The purpose of the study was to compare clinical pregnancy and delivery rates with fresh and frozen embryo transfer in patients admitted to Shiraz- Human Assisted Reproductive Center with ovarian hyperstimulation syndrome (OHSS). METHODS: OHSS patients randomly divided in two groups, group A (n=50) with fresh embryo transfer and group B (n=50) with frozen embryo transfer. We used vitrification method for freezing the embryos. Patient age, combination of female and male factors, total number of retrieved oocytes, number of cryopreserved embryo, number of transferred embryos, clinical pregnancy and delivery rates were recorded for all patients. All statistical calculations were done using SPSS software. Generalized linear model was used to adjust the confounding factors to compare the clinical pregnancy and delivery rates between two groups. The p<0.05 was considered statistically significant. RESULTS: Mean (±SD) ages of these patients were 26.78±3.5 and 28.42±4.2 yrs in fresh (A) and frozen (B) embryo transfer groups respectively. Combinations of male and female factors were 28.3% and 32.1% respectively. Average numbers of oocytes retrieved in two groups were 22.14±4.3 and 21.02±4.9, and after fertilization, embryos cryopreserved per patient yielded averages of 13.82±3.5 and 12.5±4.3. Thaw and ET were performed and the means for transferred embryos were 3.22±0.6 and 4.1±0.7. We didn't find any significant differences in implicit parameters between the two groups. The pregnancy and delivery rates in OHSS patients were significantly higher in frozen embryo transfer, 63.1% and 45.6%, compared with fresh embryo transfer, 55.1% and 35.4%, respectively. CONCLUSION: The pregnancy and delivery rates in OHSS cases, both fresh and subsequently with frozen embryo transfer, were exceptionally high. There was statistically significant difference of pregnancy and delivery rates between fresh and frozen embryo transfer. As a result, an elective embryo freezing policy to moderate the severity and duration of OHSS has compromising outcomes for women at risk of OHSS.